Spinal abscess in a patient with undiagnosed Gerbode defect: a case report. Issue 10 (15th September 2021) - Liao, Yuen Wei; Ensam, Bode; Kodamanchile, Aaditya; Duckett, Simon
Abstract: Background: Gerbode defect (GD) is a rare cardiac defect in which an abnormal communication occurs between the left ventricle and right atrium. The aetiology is usually congenital but acquired defects can occur. Case summary: We report on a 47-year-old male with atrioventricular block prior to decompression of an epidural abscess extending from the skull base to the 7th thoracic vertebrae. Following positive blood cultures for Staphylococcus aureus, a transoesophageal echocardiogram performed revealed a small GD with associated endocarditis. In our case, the defect was small and there was no evidence of heart failure, there was little guidance or literature available on how to best manage our patient. A multidisciplinary decision was taken to treat the endocarditis medically and to not close the defect in the acute setting. He recovered well and did not suffer any further cardiac complications. A repeat transthoracic echocardiogram did not reveal any evidence of endocarditis. Conclusion: Gerbode defects are rare but have been known to increase the risk of developing endocarditis. It is important to have a high clinical suspicion of endocarditis in patients with evidence of conduction disorders and systemic infection.